Kinematic analysis of soccer players in shuttle running - Padulo, J.; D'Ottavio, S.; Pizzolato, F.; Smith, L.; Annino, G. (International Journal of Sports Medicine, 2012)
The intermittent shuttle running test is mainly used within soccer to assess aerobic power. For this reason we studied kinematic parameters and heart rate at both an increasing speed, [Yo-Yo Endurance Lv 1 (Y1)] and at constant velocity [95% maximal aerobic velocity (MAV95%)]. 12 soccer players were selected for this study. A high-speed digital camera (210 Hz) was used to record motion; Dartfish5.5Pro was used to perform 2D video analysis and heart rate was also recorded and computed during the test. The parameters considered (baseline measures with respect to the end of each test) in this study were: step length (SL), contact time (CT) and heart rate (HR). SL: 40% in Y1 and - 22% in MAV95%. CT: - 31% in Y1 and 29% in MAV95%. HR: increased 96% in Y1 and 17% in MAV95%. These results highlight 2 different neuromechanical strategies adopted under fatigued conditions. In light of the clear changes of the CT in MAV95% (29%) and with respect to the moderate changes in HR (17%) it is clear that the CT is the most important parameter, as it experiences greater adaptations associated with neuromuscular patterns, under a fatigued condition as opposed to HR.